Preparation method of high-performance lignin-based composite electrode material
Patent Information
- Application Number
- CN202611383520.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]然而,直接碳化木质素所得的多孔碳电极材料往往存在导电性一般、表面活性位点不足等问题,同时其受限于纯双电层储能机理,导致其比电容和能量密度较低
[0016](1)本发明方法中,通过共价修饰策略制备季铵盐木质素,能够让金属离子在水溶液中更容易与季铵盐木质素分子上羟基的氧发生反应,形成稳定的金属-氧-碳结构,使木质素基电极材料拥有更多的电化学活性位点,提升电极材料的电化学性能。
Smart Images

Figure CN123017753A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomass-based supercapacitor technology, specifically relating to a method for preparing a high-performance lignin-based composite electrode material. Background Technology
[0002] Supercapacitors, as energy storage devices combining high power density, long cycle life, and rapid charge-discharge characteristics, play a crucial role in energy storage and conversion. A supercapacitor consists of five parts: the casing, current collector, electrode materials, separator, and electrolyte. Among these, the electrode materials are the core determinant of the supercapacitor's electrochemical performance. Currently, commercial supercapacitors primarily use high-specific-surface-area activated carbon as the electrode material. Utilizing renewable and low-cost biomass precursors to prepare porous carbon materials is an effective way to improve the cost-effectiveness and environmental friendliness of electrode materials. Lignin, as the second largest natural aromatic polymer, possesses advantages such as high carbon content, rich aromatic structures, and wide availability, and is considered a highly promising carbon precursor.
[0003] However, porous carbon electrode materials obtained by direct carbonization of lignin often suffer from problems such as general conductivity and insufficient surface active sites. Furthermore, their specific capacitance and energy density are low due to the limitation imposed by the pure double-layer energy storage mechanism. To mitigate the limitations imposed by the single energy storage mechanism, introducing transition metals to provide more pseudocapacitance to the carbon electrode material is a common strategy. Therefore, constructing stable covalent bonds between lignin molecules and transition metals has become an effective means of preparing high-performance lignin-based composite materials. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing high-performance lignin-based composite electrode materials, which improves the performance of lignin electrode materials by constructing covalent bonds.
[0005] The technical solution adopted in this invention is a method for preparing a high-performance lignin-based composite electrode material, which is implemented according to the following steps:
[0006] Step 1: Add lignin and NaOH to an Erlenmeyer flask and mix, stirring until completely dissolved. Then add 3-chloro-2-hydroxypropyltrimethylammonium chloride and stir to react. After the reaction is complete, perform reverse precipitation and vacuum drying to obtain quaternary ammonium lignin.
[0007] Step 2: Immerse quaternary ammonium lignin in a transition metal ion solution and stir to react. After the reaction is complete, perform reverse precipitation and vacuum drying to obtain the composite material;
[0008] Step 3: The composite material is placed in a tube furnace for carbonization. The resulting carbonized material is then mixed with an alkali metal compound and ground to obtain a mixture. The mixture is then activated at high temperature in a tube furnace. After activation, the material is washed with deionized water until the pH is neutral, filtered, and dried to obtain the lignin-based composite electrode material.
[0009] Step 4: Grind the lignin-based composite material with the conductive agent, binder and dispersion in an agate mortar into a slurry. Coat the slurry evenly on the current collector and dry it to obtain the lignin-based composite electrode.
[0010] The invention is further characterized in that,
[0011] In step 1, the mass of lignin is 1-20 g; the volume of NaOH is 100-300 mL with a concentration of 0.2-0.6 M; the volume of 3-chloro-2-hydroxypropyltrimethylammonium chloride is 1-10 mL; and the reaction is stirred at 70-90 °C for 2-6 h. After the reaction is complete, 5-15 wt% K3Fe(CN)6 and 30-40 wt% HCl are added dropwise to the system for reverse precipitation, and the mixture is dried in a vacuum drying oven at 40-80 °C for 6-10 h.
[0012] In step 2, 1–5 g of quaternary ammonium lignin is immersed in 50–200 mL of a 1–8 M transition metal ion solution and stirred at 60–80 °C for 4–8 h; the transition metal ion is Zn. 2+ Cu 2+ Mn 2+ Any one of the following; the anti-precipitation conditions are the same as in step 1, drying in a vacuum drying oven at 60-80 ℃ for 8-12 h.
[0013] In step 3, both carbonization and activation are carried out under a nitrogen atmosphere, with a nitrogen flow rate of 20–60 mL / min; the heating rate is 1–10 ℃ / min, the carbonization temperature is 1000–1200 ℃, and the holding time is 30–200 min; the activation temperature is 600–1000 ℃, and the holding time is 40–160 min; the cooling rate is 5–15 ℃ / min; any one of KOH, NaOH, and CaCl2 can be used as the alkali metal compound; the mass ratio of the composite material to the alkali metal compound is 1:1–4.
[0014] In step 4, the lignin-based composite material, conductive agent, and binder are in a mass ratio of 80-90:5-15:5-15; the conductive agent can be any one of conductive carbon black, graphene, or acetylene black; the binder can be any one of polytetrafluoroethylene dispersion, polyvinylidene fluoride, or polyvinyl alcohol; and the current collector can be any one of nickel foam, copper foil, or carbon cloth.
[0015] The beneficial effects of this invention are:
[0016] (1) In the method of the present invention, the preparation of quaternary ammonium lignin by covalent modification strategy can make it easier for metal ions to react with oxygen on the hydroxyl group of quaternary ammonium lignin molecule in aqueous solution to form a stable metal-oxygen-carbon structure, so that the lignin-based electrode material has more electrochemical active sites and improves the electrochemical performance of the electrode material.
[0017] (2) This invention uses renewable and low-cost lignin as the main carbon source, which is green and sustainable. Attached Figure Description
[0018] Figure 1 This is the CV curve of the unmodified lignin electrode material in the method of this invention;
[0019] Figure 2 The CV curve of the Cu-quaternary ammonium salt lignin-based composite electrode material in the method of this invention;
[0020] Figure 3 The GCD curve of the Mn-quaternary ammonium salt lignin-based composite electrode material in the method of this invention;
[0021] Figure 4 The Nyquist curve of the Mn-quaternary ammonium salt lignin-based composite electrode material in the method of this invention;
[0022] Figure 5 The specific capacitance retention curve of the Zn-quaternary ammonium salt lignin-based composite electrode material in the method of this invention;
[0023] Figure 6 This is a long-cycle test curve of the asymmetric supercapacitor Zn-LC / / LC assembled in the method of this invention. Detailed Implementation Plan
[0024] The present invention will now be described in detail with reference to specific embodiments and accompanying drawings.
[0025] This invention relates to a method for preparing a high-performance lignin-based composite electrode material, which is implemented according to the following steps:
[0026] Step 1: Add lignin and NaOH to an Erlenmeyer flask and mix, stirring until completely dissolved. Then add 3-chloro-2-hydroxypropyltrimethylammonium chloride and stir to react. After the reaction is complete, perform reverse precipitation and vacuum drying to obtain quaternary ammonium lignin.
[0027] The mass of lignin is 1-20 g;
[0028] The volume of NaOH is 100–300 mL, and the concentration is 0.2–0.6 M.
[0029] The volume of 3-chloro-2-hydroxypropyltrimethylammonium chloride is 1–10 mL;
[0030] The reaction was stirred at 70–90 °C for 2–8 h.
[0031] After the reaction was completed, 5-15 wt% K3Fe(CN)6 and 30-40 wt% HCl were added dropwise to the system for reverse precipitation, and the system was dried in a vacuum drying oven at 40-80 °C for 6-10 h.
[0032] Step 2: Immerse quaternary ammonium lignin in a transition metal ion solution, stir to react, and after the reaction is completed, perform reverse precipitation and vacuum drying to obtain the composite material.
[0033] The mass of quaternary ammonium lignin is 1-5 g, which is immersed in 50-200 mL of 1-8 M transition metal ion solution and stirred at 60-80 °C for 4-8 h;
[0034] The transition metal ion is Zn 2+ Cu 2+ Mn 2+ Any one of them;
[0035] The anti-precipitation conditions are the same as in step 1: drying in a vacuum drying oven at 60–80 °C for 8–12 h.
[0036] Step 3: Place the composite material in a tube furnace for carbonization, then mix and grind the resulting carbonized material with an alkali metal compound to obtain a mixture. Place the mixture in a tube furnace for high-temperature activation. After activation, wash the material with deionized water until the pH is neutral, filter, and dry to obtain the lignin-based composite electrode material.
[0037] Carbonization and activation were both carried out under a nitrogen atmosphere, with a nitrogen flow rate of 20–60 mL / min.
[0038] Heating rate: 1–10 °C / min; carbonization temperature: 1000–1200 °C; holding time: 30–200 min; activation temperature: 600–1000 °C; holding time: 40–160 min; cooling rate: 5–15 °C / min.
[0039] The alkali metal compound can be any one of KOH, NaOH, or CaCl2;
[0040] The mass ratio of the composite material to the alkali metal compound is 1:1 to 4;
[0041] Step 4: Grind the lignin-based composite material with the conductive agent, binder and dispersion in an agate mortar into a slurry, coat the slurry evenly on the current collector and dry it to obtain the lignin-based composite electrode.
[0042] The lignin-based composite material, conductive agent, and binder are disposed in a mass ratio of 80-90:5-15:5-15;
[0043] The conductive agent can be any one of conductive carbon black, graphene, or acetylene black;
[0044] The binder is any one of polytetrafluoroethylene dispersion, polyvinylidene fluoride, and polyvinyl alcohol;
[0045] The current collector can be any one of nickel foam, copper foil, or carbon cloth.
[0046] Example 1
[0047] 10 g of lignin was mixed with 100 mL of 0.4 M NaOH in an Erlenmeyer flask and stirred until completely dissolved. Then, 5 mL of 3-chloro-2-hydroxypropyltrimethylammonium chloride was added, and the mixture was stirred at 80 °C for 6 h. After the reaction was complete, 10 wt% K3Fe(CN)6 and 37 wt% HCl were added dropwise to the system. After complete precipitation, the mixture was dried in a vacuum drying oven at 50 °C for 8 h to obtain quaternary ammonium lignin. 3 g of quaternary ammonium lignin was immersed in 125 mL of 4.0 M CuCl2 solution and stirred at 65 °C for 6 h to obtain CuCl2. 2+ Covalent doping was performed. The anti-precipitation conditions were the same as in step 1. The precipitate was dried in a vacuum drying oven at 60 °C for 12 h to obtain Cu-L. Cu-L was placed in a tube furnace and heated to 1200 °C at a rate of 4 °C / min under a nitrogen atmosphere of 20 mL / min, held for 120 min, and then cooled to room temperature at a rate of 10 °C / min to obtain the carbonized material. The obtained carbonized material was then mixed with KOH at a mass ratio of 1:1.5 and ground to obtain a mixture. The mixture was placed in a tube furnace and activated by heating to 800 °C at 5 °C / min and holding for 120 min. After activation, the material was washed with deionized water until the pH was neutral, filtered, and dried to obtain Cu-LC. The active material was mixed with conductive carbon black and polytetrafluoroethylene dispersion at a mass ratio of 80:10:10, and then ground into a slurry in an agate mortar. The slurry was then uniformly coated onto nickel foam and dried to obtain the Cu-LC electrode material. The CV curves of the electrode materials before and after modification were tested in a three-electrode system. Figure 1 The CV curves for the unmodified lignin electrode material exhibit a near-parallelogram shape, indicating that its energy storage mechanism is a typical double-layer type. As the scan rate increases, the integral area of the curve also increases. Figure 2 The CV curves for the Cn-LC electrode material show obvious redox peaks, attributed to the introduction of Cu. (Comparison) Figure 1 and Figure 2The integral area of the CV curve at the same scan rate shows that the Cu-LC electrode material has stronger energy storage performance.
[0048] Example 2
[0049] 8 g of lignin was mixed with 80 mL of 0.4 M NaOH in an Erlenmeyer flask and stirred until completely dissolved. Then, 4 mL of 3-chloro-2-hydroxypropyltrimethylammonium chloride was added, and the mixture was stirred at 75 °C for 8 h. After the reaction was complete, 5 wt% K3Fe(CN)6 and 37 wt% HCl were added dropwise to the system. After complete precipitation, the mixture was dried in a vacuum drying oven at 50 °C for 8 h to obtain quaternary ammonium lignin. 4 g of quaternary ammonium lignin was immersed in 150 mL of 4.0 M MnCl2 solution and stirred at 75 °C for 4 h to obtain MnCl2. 2+ Covalent doping was performed. The anti-precipitation conditions were the same as in step 1. The precipitate was dried in a vacuum drying oven at 50 °C for 8 h to obtain Mn-L. Mn-L was placed in a tube furnace and heated to 1100 °C at a nitrogen flow rate of 25 mL / min, held for 120 min, and then cooled to room temperature at a rate of 10 °C / min to obtain the carbonized material. The obtained carbonized material was then mixed with KOH at a mass ratio of 1:2 and ground to obtain a mixture. The mixture was placed in a tube furnace and activated by heating to 800 °C at 5 °C / min and holding for 150 min. After activation, the material was washed with deionized water until the pH was neutral, filtered, and dried to obtain Mn-LC. The active material was mixed with conductive carbon black and polytetrafluoroethylene dispersion at a mass ratio of 85:10:5 and then ground into a slurry in an agate mortar. The slurry was then evenly coated onto nickel foam and dried to obtain the Mn-LC electrode material. Figure 3 The GCD curves of the Mn-LC electrode material at different current densities were measured in a three-electrode system. The images show a clear charge-discharge plateau, a typical pseudocapacitive characteristic, indicating that the transition metal Mn has successfully composited with the lignin-based carbon material. Figure 4 In the Nyquist curves, the intersection of the high-frequency curve with the real axis represents the equivalent series resistance (Rs), the diameter of the semicircle in the mid-frequency region represents the charge transfer resistance (Rct), and the slope in the low-frequency region represents the ion diffusion resistance. The figure shows that the modified Mn-LC electrode material has a lower Rs of 0.43 Ω, while the Rct of Mn-LC is larger in the mid-frequency region. This may be because the addition of the transition metal reduces the conductivity of the carbon material. In the low-frequency region, both the modified and unmodified electrode materials exhibit good ion diffusion capabilities.
[0050] Example 3
[0051] 9 g of lignin was mixed with 90 mL of 0.4 M NaOH in an Erlenmeyer flask and stirred until completely dissolved. Then, 5 mL of 3-chloro-2-hydroxypropyltrimethylammonium chloride was added, and the mixture was stirred at 70 °C for 8 h. After the reaction was complete, 7 wt% K3Fe(CN)6 and 37 wt% HCl were added dropwise to the system. After complete precipitation, the mixture was dried in a vacuum drying oven at 50 °C for 8 h to obtain quaternary ammonium lignin. 3 g of quaternary ammonium lignin was immersed in 120 mL of 4.0 M MnCl2 solution and stirred at 70 °C for 5 h to react with Zn. 2+ Covalent doping was performed. The anti-precipitation conditions were the same as in step 1. The precipitate was dried in a vacuum drying oven at 55 °C for 7 h to obtain Mn-L. The Mn-L was placed in a tube furnace and heated to 1200 °C at a rate of 4 °C / min under a nitrogen atmosphere of 20 mL / min, held for 120 min, and then cooled to room temperature at a rate of 15 °C / min to obtain the carbonized material. The obtained carbonized material was then mixed with KOH at a mass ratio of 1:1 and ground to obtain a mixture. The mixture was placed in a tube furnace and activated by heating to 800 °C at 4 °C / min and holding for 130 min. After activation, the material was washed with deionized water until the pH was neutral, filtered, and dried to obtain Zn-LC. The active material was mixed with conductive carbon black and polytetrafluoroethylene dispersion at a mass ratio of 80:15:5, and then ground into a slurry in an agate mortar. The slurry was then uniformly coated onto nickel foam and dried to obtain the Zn-LC electrode material. Electrochemical tests were performed on the obtained material to obtain the specific capacitance before and after modification. The specific capacitance values at different current densities were calculated, and the specific capacitance retention curve was plotted as follows: Figure 5 As shown in the figure, when the current density increases by 20 times, the specific capacitance of the modified Zn-LC reaches 233.5 A / g at a current density of 0.5 A / g, which is 6 times higher than that of the unmodified LC. When the current density increases by 20 times, the specific capacitance retention rate of Zn-LC remains at 77.77%. Using Zn-LC as the positive electrode and LC as the negative electrode, an asymmetric supercapacitor Zn-LC / / LC was assembled. Figure 6 The figures show the charge-discharge cycle curves of Zn-LC / / LC at a current density of 10 A / g for 100 million cycles. After 10000 charge-discharge cycles, the specific capacitance retention rate can still reach more than 90%, which is attributed to the stable covalent bond between Zn and lignin molecules, effectively preventing the shedding of active material during charge and discharge.
[0052] The mechanism of action of this invention is as follows: First, the hydroxyl group on the benzene ring of the lignin side chain loses a -H under alkaline conditions. + Get -O - -O on the lignin benzene ring -Attacking the carbon at the 3-position of 3-chloro-2-hydroxypropyltrimethylammonium chloride generates quaternary ammonium lignin. Adding a solution of transition metal ions allows these ions to coordinate with the lone pair of electrons in the hydroxyl group of the quaternary ammonium lignin, forming a stable MOC bond. This successful covalent doping of the metal into the lignin molecule achieves this goal. The metal provides redox electron pairs, introducing a large amount of pseudocapacitance into the lignin-based carbon electrode material, thereby enhancing its electrochemical performance.
[0053] The reaction of lignin with 3-chloro-2-hydroxypropyltrimethylammonium chloride is because the resulting quaternary ammonium salt lignin has good water solubility, making it easier to react with transition metal ions in the second step of the reaction.
Claims
1. A method for preparing a high-performance lignin-based composite electrode material, characterized in that, The specific steps are as follows: Step 1: Add lignin and NaOH to an Erlenmeyer flask and mix, stirring until completely dissolved. Then add 3-chloro-2-hydroxypropyltrimethylammonium chloride and stir to react. After the reaction is complete, perform reverse precipitation and vacuum drying to obtain quaternary ammonium lignin. Step 2: Immerse quaternary ammonium lignin in a transition metal ion solution and stir to react. After the reaction is complete, perform reverse precipitation and vacuum drying to obtain the composite material. Step 3: The composite material is carbonized in a tube furnace. After carbonization, it is ground and mixed with alkali metal compounds, then activated in a tube furnace. Finally, it is washed with deionized water until the pH is neutral, filtered, and dried to obtain the lignin-based composite electrode material. Step 4: Grind the lignin-based composite electrode material with the conductive agent, binder and dispersion in an agate mortar into a slurry. Coat the slurry evenly on the current collector and dry it to obtain the lignin-based composite electrode.
2. The method for preparing a high-performance lignin-based composite electrode material according to claim 1, characterized in that, In step 1, the mass of lignin is 1–20 g; the volume of NaOH is 100–300 mL with a concentration of 0.2–0.6 M; the volume of 3-chloro-2-hydroxypropyltrimethylammonium chloride is 1–10 mL; and the reaction is stirred at 70–90 °C for 2–6 h. After the reaction is complete, 5–15 wt% K3Fe(CN)6 and 30–40 wt% HCl are added dropwise to the system for reverse precipitation, and the mixture is dried in a vacuum drying oven at 40–80 °C for 6–10 h.
3. The method for preparing a high-performance lignin-based composite electrode material according to claim 1, characterized in that, In step 2, 1–5 g of quaternary ammonium lignin is immersed in 50–200 mL of a 1–8 M transition metal ion solution and stirred at 60–80 °C for 4–8 h; the transition metal ion is Zn. 2+ Cu 2+ Mn 2+ Any one of the following; the anti-precipitation conditions are the same as in step 1, drying in a vacuum drying oven at 60-80 ℃ for 8-12 h.
4. The method for preparing a high-performance lignin-based composite electrode material according to claim 1, characterized in that, In step 3, both carbonization and activation are carried out under a nitrogen atmosphere, with a nitrogen flow rate of 20–60 mL / min; the heating rate is 1–10 ℃ / min, the carbonization temperature is 1000–1200 ℃, and the holding time is 30–200 min; the activation temperature is 600–1000 ℃, and the holding time is 40–160 min; the cooling rate is 5–15 ℃ / min; any one of KOH, NaOH, and CaCl2 can be used as the alkali metal compound; the mass ratio of the composite material to the alkali metal compound is 1:1–4.
5. The method for preparing a high-performance lignin-based composite electrode material according to claim 1, characterized in that, In step 4, the lignin-based composite electrode material, conductive agent, and binder are in a mass ratio of 80-90:5-15:5-15; the conductive agent can be any one of conductive carbon black, graphene, or acetylene black; the binder can be any one of polytetrafluoroethylene dispersion, polyvinylidene fluoride, or polyvinyl alcohol; and the current collector can be any one of nickel foam, copper foil, or carbon cloth.